1986
DOI: 10.1007/bf00439403
|View full text |Cite
|
Sign up to set email alerts
|

Generalized soft tissue calcification in children and adolescents with end stage renal failure

Abstract: Sixteen children and adolescents undergoing regular haemodialysis treatment were studied for the occurrence of metastatic calcifications. By the use of diphosphonate bone-scanning, roentgenography of the chest and skull and ocular slit lamp examination, generalized visceral calcification was diagnosed in two patients. No relationship between visceral calcification and biochemical, radiological or histological abnormalities of renal osteodystrophy was found. Our study demonstrates that visceral calcification al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Uptake of diphosphonates appears to be uncommon in the myocardial region, as it was not reported in the series of patients mentioned above (Sy and Mittal 1975;Conger and Alfrey 1976;Olgaard et al 1976;Velentzas et al 1978;Faubert et al 1980;Drachman et al 1986;Van Diemen-Steenvoorde et al 1986). In a survey of case reports of patients with diffuse uptake in pulmonary calcifications (Choy and Murray 1980), only 5 of the 26 patients studied also showed uptake in the myocardial region, and only 1 of these 5 was a patient on chronic haemodialysis.…”
Section: Cardiac Calcificationsmentioning
confidence: 67%
See 1 more Smart Citation
“…Uptake of diphosphonates appears to be uncommon in the myocardial region, as it was not reported in the series of patients mentioned above (Sy and Mittal 1975;Conger and Alfrey 1976;Olgaard et al 1976;Velentzas et al 1978;Faubert et al 1980;Drachman et al 1986;Van Diemen-Steenvoorde et al 1986). In a survey of case reports of patients with diffuse uptake in pulmonary calcifications (Choy and Murray 1980), only 5 of the 26 patients studied also showed uptake in the myocardial region, and only 1 of these 5 was a patient on chronic haemodialysis.…”
Section: Cardiac Calcificationsmentioning
confidence: 67%
“…Gastric uptake was also reported by Venkatesh et al (1978) in 2 dialysis patients and by Goldstein et al (1984) in an additional dialysis patient. Van Diemen-Steenvoorde et al (1986) further demonstrated increased gastric uptake in 1 of the 16 patients they studied. Gastric uptake was not reported in any of the other series of patients (Sy and Mittal 1975;Conger and Alfrey 1976;Olgaard et al 1976;De Graaf et al 1979a, b;Faubert et al 1980;Drachman et al 1986).…”
Section: Gastric Calcificationsmentioning
confidence: 99%